Islamic Spirituality and Coexistence In Diverse Learning Contexts: Educational Insights From Islamic Philosophy - Donna Aprilia; Akhmad Affandi (Halaqa: Journal of Islamic Education, 2026)
This article explores the contribution of Islamic spirituality in fostering peaceful coexistence within diverse learning contexts. Drawing from Islamic philosophy of education, this study analyzes theological, ethical, and epistemological values that strengthen inclusivity and harmony in multicultural classrooms. Employing a qualitative approach through literature review and philosophical interpretation, the findings reveal that Islamic spirituality—rooted in tawhid (divine unity), adab (ethical conduct), and rahmah (compassion)—can foster a tolerant and transformative collective consciousness. The article recommends integrating Islamic spiritual values into educational curricula and pedagogical practices as a strategic step toward enhancing social cohesion through education.